(untitled) - 1984-; Stowell, Austin; 1936-; Alda, Alan; Ryan, Amy; Rylance, Mark; Spielberg, Steven; Hanks, Tom; Charman, Matt; 1946; Coen, Ethan; Coen, Joel (Burbank, CA, 2016)
James Donovan is a Brooklyn lawyer who finds himself thrust into the center of the Cold War when the CIA sends him on the near-impossible task to negotiate the release of a captured American U-2 pilot.
MPAA rating: PG-13; for some violence and brief strong language
CHV rating: PG
Keywords: Drama; 1916-1970; Donovan, James B; Drama; 1929-1977; Powers, Francis Gary; Drama; Prisoners of war; Drama; Cold War; Drama; U-2 Incident, 1960; Drama; Hostage negotiations; Drama; Espionage